Analysis of Aerospace and Defense Industry- UK - Maity, Amitkumar (2012)
In order to test the performance of A&D sector of UK following data are taken into consideration. The past 10 years information on revenue, P/E ratio, EPS (Earning Per Share) Return on Shareholders fund, Liquidity ratio, share price for the companies featured in FTSE100. Also in order to see its performance I have tried to compare A&D sector with other sectors like Pharmaceuticals and Biotechnology, Food producers, Real Estate Investment Trust, Support Services on same parameters. Further analyzing A&D sector in depth based on EV/EBITA (EV Multiple) and analyzing the development prospects in future based on the factors (financial & non- financial) that plays an important and have direct impact on the performance of company.